Paediatric neuro-oncology rehabilitation in the UK: carer and provider perspectives - David Walker; Bethan Treadgold; Colin Kennedy; Helen Spoudeas; Elaine Sugden; Kim Bull (BMJ Publishing Group, 2019)
Objective The provision of rehabilitation services after childhood brain tumour has not been established, despite a recent parliamentary call for urgent action. This service evaluation aimed to determine what specialist paediatric neuro-oncology rehabilitation services were available across the UK at the time of the surveys and whether the needs of patients and their families were being met.Design Cross-sectional on-line surveys.Participants Survey 1: neuro-oncologist and nurse specialist members of the Children's Cancer and Leukaemia Group (CCLG) at Children's Principle Treatment Centres (PTCs) in the UK; Survey 2: parents of paediatric neuro-oncology patients belonging to The Brain Tumour Charity (TBTC) Research Involvement Network (RIN).Results 17 of the 20 (85%) PTCs in the UK and two teenagers and young adult cancer units responded to Survey 1, and 17 members of TBTC's RIN responded to Survey 2. Access to inpatient and outpatient neuro-oncology rehabilitation services after treatment for a central nervous system (CNS) tumour varied across regions in the UK. Service users in the RIN identified a need for an established neuro-oncology rehabilitation service for young people, a need for better communication across services and with families, and a need to fill gaps in multidisciplinary teams.Conclusion The urgent need for specialist paediatric, teenage and young adult neuro-oncology rehabilitation services in the UK is often unmet, particularly for outpatients. Where services are not provided for those children and young people disadvantaged by the diagnosis of a CNS tumour, in clear breach of current guidelines, remedial action needs to be taken to ensure appropriate and equal access.